Bank leverage cycles - Galo Nu\~no; Carlos Thomas (European Central Bank (ECB), 2013)
We document the cyclical dynamics in the balance sheets of US leveraged financial intermediaries in the post-war period. Leverage has contributed more than equity to fluctuations in total assets. All three variables are several times more volatile than GDP. Leverage has been positively correlated with assets and (to a lesser extent) GDP, and negatively correlated with equity. These findings are robust across financial subsectors. We then build a general equilibrium model with banks subject to endogenous leverage constraints, and assess its ability to replicate the facts. In the model, banks borrow in the form of collateralized risky debt. The presence of moral hazard creates a link between the volatility in bank asset returns and bank leverage. We find that, while standard TFP shocks fail to replicate the volatility and cyclicality of leverage, volatility shocks are relatively successful in doing so.
Keywords: E20; G10; G21; 330; call option; cross-sectional volatility; Financial intermediaries; leverage; limited liability; Moral Hazard; put option; short-term collateralized debt